Islamic governance in action: Malaysia's approach to Rohingya refugee Islamic-based assistance - Aizat Khairi; Andika Ab. Wahab; Mohd Na'eim Ajis; Mohd Ramlan Mohd Arshad (Penerbit Universiti Kebangsaan Malaysia, 2024)
This study examines Malaysia's Islamic governance mechanisms in addressing the challenges confronted by Rohingya refugees, focusing on the roles of Jabatan Agama Islam Selangor (JAIS) and Jabatan Kemajuan Islam Malaysia (JAKIM). Employing a qualitative approach with a case study design, the research explores Malaysia's intricate response to the Rohingya refugee crisis, speciHically in Kuala Lumpur and Selangor. The purposive sampling method involves engaging JAKIM and JAIS ofHicers, offering valuable insights into Islamic governance structures. The research methodology includes content analysis of ofHicial documents, policies, and interactions with key stakeholders, aiming to illuminate the holistic approach of Islamic governance in addressing religious, legal, educational, and welfare aspects of Rohingya refugee assistance. Key Hindings unveil the roles played by JAIS and JAKIM in empowering Rohingya refugees, particularly in education and religious affairs.. Through content analysis, the research provides a comprehensive understanding of the challenges, successes, and gaps in Malaysia's Islamic governance response to the Rohingya refugee crisis. The research advocates for collaborative efforts and policy enhancements to ensure a more inclusive and compassionate environment for refugees within the Islamic context